The Relevance of Sexual Dysfunction Related to Groin Pain After Inguinal Hernia Repair – The SexIHQ Short Form Questionnaire Assessment - Gutlic, Nihad; Petersson, Ulf; Rogmark, Peder; Montgomery, Agneta (Frontiers in Surgery, 2018)
Background Chronic postoperative pain after inguinal hernia surgery can affect sexual function. A new short form questionnaire for inguinal hernia pain related sexual dysfunction (SexIHQ) was introduced and applied to a register based cohort of total extra-peritoneal hernioplasty (TEP) operated patients. Methods Sexually active men, 30–60 years old, recorded in the Swedish Hernia Register for a primary inguinal hernia TEP operation were included. Two initial questions of the SexIHQ identify patients with pain at sexual activity. Only these patients proceeded to answer the specific questions on pain-induced impairment of sexual activity, pain frequency and intensity, physical functions (erection and ejaculation), and symptoms of depression. SexIHQ, the Short Form-36 (SF-36), the Inguinal Pain Questionnaire (IPQ) were mailed to participants for long term follow up. Results In 538 included patients, 44 (8.2%) reported pain during sexual activity at mean 33 months after surgery. Sexual dysfunction was seen in 33 of these patients. A postoperative complication was a risk factor for pain during sexual activity; OR 4.89 (95% CI 1.92–12.43; p<0.001). Quality-of-life was reduced in almost all SF-36 domains in patients with pain during sexual activity. Conclusions A short form questionnaire, suitable for large cohorts, was developed to assess sexual dysfunction due to groin pain after inguinal hernia repair in male patients. Sexual dysfunction due to groin pain after hernia surgery by TEP is surprisingly common. Patients should preoperatively be informed of the risk of having pain during sexual activity following groin hernia surgery.